PENGARUH DISIPLIN KERJA, BUDAYA ORGANISASI DAN INSENTIF TERHADAP KINERJA KARYAWAN DI PT LIXICON INDONESIA - Novelina, Novelina Stephani; Husein, Alice Erni (SCIENTIA JOURNAL, 2025)
This Study aims to examine the impact of work discipline, organizational culture, and incentives on employee perfomance at PT. Lixicon Indonesia, A Contracting company based in Batam City, Riau Islands, Indonesia. Employee perfomance plays a cricital role in ensuring organizational success, particulary in competitive industries. The research adopts a quantitative approach, utilizing surveys distributed to employees across various departments at PT. Lixicon Indonesia. The data is analyzed using multiple regression analysis to determine the individual and collective effects of work discipline, organizational culture, and incentives on employee perfomance with the help of SPSS 29 software. The findings reveal that work discipline significantly enhances employee performance by fostering a sense of responsibility and adherence to company policies, contributing 24.7% to performance improvement. Organizational culture also plays a pivotal role, significantly boosts motivation and productivity, accounting for 42.6% of the performance increase.  Additionally, incentives, both financial and non-financial, are found to act as strong motivators that boost performance when aligned with employees' expectations and company goals, contributing 57.8%.  Simultaneously, these three variables contributed 84.8% to the improvement of employee performance at PT. Lixicon Indonesia, while the remaining 15.2% was influenced by other factors outside this study. The study concludes that three factors collectively contribute to optimizing employee perfomance and recommends strategies for improving their implementation at PT. Lixicon Indonesia.